Identifying Stuttering in Arabic Speakers Who Stutter: Development of a Non-word Repetition Task and Preliminary Results - Alsulaiman, Roaa; Harris, John; Bamaas, Sarah; Howell, Peter (Frontiers in Pediatrics, 2022)
Stuttering and other conditions that affect speech fluency need to be identified at an early age in order that effective interventions can be given before the problems becomes chronic. This applies in countries where several languages are spoken including those in which English and Arabic are both widely used which calls for assessment procedures that work across these languages. The ‘universal' non-word repetition task (UNWR) has been established as an effective screening tool for discriminating between children who stutter (CWS) and children with word-finding difficulty for a number of languages. However, the UNWR does not apply to languages such as Arabic and Spanish. The present study aimed to: (1) introduce an Arabic English NWR (AEN_NWR); which was developed based on the same phonologically informed approach used with UNWR; (2) present preliminary non-word repetition data from Arabic-speaking CWS and adults who stutter (AWS). The AEN_NWR items comprises twenty-seven non-words that meet lexical phonology constraints across Arabic and English. The set of items includes non-words of two, three and four syllables in length. Preliminary non-word repetition data were collected from ten CWS between the ages of 6;5 and 16;7 (Mage = 12:1) and fourteen AWS between the ages of 19;2 and 31;0 (Mage = 24). Participants performed the non-word repetition task and provided a sample of spontaneous speech. The spontaneous speech samples were used to estimate %stuttered syllables (%SS). To validate that AEN_NWR performance provides an alternative way of assessing stuttering, a significant correlation was predicted between %SS and AEN_NWR performance. Also, word length should affect repetition accuracy of AEN_NWR. As predicted, there was a significant negative correlation between the AEN_NWR and %SS scores (r (25) = −0.5), p < 0.000). Overall, CWS were less accurate in their repetition than AWS at all syllable lengths. The AEN_NWR provides a new assessment tool for detecting stuttering in speaker of Arabic and English. Future studies would benefit from a larger sample of participants, and by testing a population-based sample. These studies would allow further investigation of the AEN_NWR as a screening measure for stuttering in preschool children.